Is global health truly global? A hashtag analysis of #GlobalHealth disparities on X - Arshad, Zara; Sharma, Pranav; Sharma, Shweta; Cheema, Mustafa Sajjad; Agarwal, Charu; Tango, Tamara; Matin, Farhan Bin; Atanasov, Atanas G.; Siddiquea, Bodrun Naher; Matin, Maima; Adamska, Olga; Stolarczyk, Artur; et al. (Frontiers in Public Health, 2024)
BackgroundX (Formerly known as Twitter) healthcare hashtags are a popular healthcare informatics and educational tool among medical professionals. #Globalhealth is one such widely used hashtag with extensive engagement. This study analyses #GlobalHealth to understand its pattern, global digital distribution, and other parameters during the COVID-19 pandemic on X.MethodsData was collected by utilizing posts using #GlobalHealth on X from 1st December 2019 to 1st November 2022. The analysis was performed using Symplur Signals to assess several parameters, such as the cumulative number of posts, impressions, category of users, co-occurring hashtags, and geolocation. The Symplur Rank system was used to assess the impact of influencers using the hashtag.ResultsA total of 843,762 posts were shared by 150,408 X users, with 4,639,144,304 impressions. Most posts (73.8%) were made by unclassified accounts, followed by doctors (4.2%), followed by other health workers. The #COVID19 was the most common co-occurring hashtag (43%). The top locations and the most influential X users came from the United States, the United Kingdom, and Canada. Among the top 25 most influential handles, a maximum (N = 09) were based in the United States—most profiles (N = 10) were categorized as international organizations followed by journals (N = 03).ConclusionThe study gives a glimpse into the discrepancies in global distribution and stakeholders of #GlobalHealth. Most posts originated from the global north, which hints at how the trend to #GlobalHealth is not perhaps as global as it is thought to be, and it also reflects upon the real-world scenarios in the context of Global Health Equity. Thus, deeper and wider studies on this digital discrepancy may add more to the existing discourse on the topic.